Analysis of Gas‐Bearing Properties of Shale Reservoirs: A Comprehensive Analysis Based on Field Interpretation and Logging Interpretation - Jin Pang; Tongtong Wu; Xinan Yu; Chunxi Zhou; Pei Yu; Haotian Chen; Jiaao Gao (Energy Science & Engineering)
ABSTRACT Shale gas, as an important component of unconventional natural gas, plays a crucial role in resource development. This paper proposes a comprehensive analytical method that combines field analysis and well logging interpretation to evaluate gas content in shale reservoirs. Core analysis experiments are conducted to obtain microscopic gas content data, and well logging parameters are calibrated and extended to reveal vertical and lateral distribution characteristics of the reservoir. In the analysis of typical wells in the study area, it is found that gas content in shale gas reservoirs is significantly influenced by total organic carbon (TOC) content, mineral composition, and pore characteristics. Micro‐pores and meso‐pores mainly store adsorbed gas, while macro‐pores and micro‐fractures are the primary storage space for free gas. The content of clay minerals significantly suppresses the total gas content and free gas volume, while quartz and TOC content enhance the gas storage capacity of the reservoir. The comprehensive analytical method proposed in this paper overcomes the limitations of single methods and establishes a framework for evaluating gas content in shale gas reservoirs from microscopic to macroscopic scales, providing a scientific basis for resource potential assessment and development planning.